Scientific realism and the rationality of science - Sankey, Howard (Ashgate, 2008)
Scientific realism -- The god's eye point of view -- Truth and entity realism -- Incommensurability and the language of science -- Induction and natural kinds -- Methodological pluralism, normative naturalism and the realist aim of science -- Realism, method and truth -- Why is it rational to believe scientific theories are true?